2019
DOI: 10.1021/acs.biochem.8b01085
|View full text |Cite
|
Sign up to set email alerts
|

New Conformations of Acylation Adducts of Inhibitors of β-Lactamase from Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis (Mtb), the main causative agent of tuberculosis (TB), is naturally resistant to β-lactam antibiotics due to the production of the extended spectrum β-lactamase BlaC. β-Lactam/β-lactamase inhibitor combination therapies can circumvent the BlaC-mediated resistance of Mtb and are promising treatment options against TB. However, still little is known of the exact mechanism of BlaC inhibition by the β-lactamase inhibitors currently approved for clinical use, clavulanic acid, sulbactam, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 52 publications
(142 reference statements)
2
38
4
Order By: Relevance
“…[33][34][35][36] Some β-lactam BlaC inhibitors were not computed in this work since they don't possess the same core structure. [37] The covalent bond is built between the serine hydroxyl and the lactam carbonyl using a new residue SEP with force filed parameters only suitable for these specific carbapenem structures. Opportunely, these parameters gave proper binding free energy values in agreement with the experimental data and were successfully applied to the MD simulations of these carbapenems.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] Some β-lactam BlaC inhibitors were not computed in this work since they don't possess the same core structure. [37] The covalent bond is built between the serine hydroxyl and the lactam carbonyl using a new residue SEP with force filed parameters only suitable for these specific carbapenem structures. Opportunely, these parameters gave proper binding free energy values in agreement with the experimental data and were successfully applied to the MD simulations of these carbapenems.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that esterase enzymes can be phosphorylated at their nucleophilic serine residues upon exposure to organophosphates through a mechanism of inactivation followed by aging [31,32,33,34]. However, there was no precedence in the literature for the phosphorylation of the active site serine of BlaC, thus it was unknown whether the Ser-70 of BlaC could be irreversibly modified by a phosphorus ligand.…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion time is fast enough that 66 ms after mixing all non-covalently bound SUB molecules in subunits B and D have reacted to the covalently bound trans -EN. This is quite unexpected as it was suggested that it would take minutes for the enamine to form after binding of SUB in the BlaC ( 3234 ). Although the SUB binds non-covalently to the active sites in subunits A and C, the reaction with the Ser-70 did not occur within ΔT mi = 66 ms.…”
Section: Inhibitor Binding and Reactionmentioning
confidence: 96%
“…Most abundant is the so-called trans-enamine (trans-EN) species (Scheme S1, compound III) that inhibits β-lactamases and helps to eliminate β-lactamase induced antibiotic resistance. The static structures of trans -ENs with β-lactamases, including BlaC, were recently characterized ( 33, 34 ) but structures of the early species that form during SUB binding remain elusive.…”
Section: Mix-and-inject Experiments At the Euxfelmentioning
confidence: 99%
See 1 more Smart Citation